Glycerol hyperhydration, endurance performance and cardiovascular and thermoregulatory responses: a case study of a highly trained triathlete - Goulet, E.; Gauthier, P.; Labrecque, S.; Royer, D. (Journal of Exercise Physiology online, 2002)
This case study observed the effect of glycerol hyperhydration (GH) in a highly trained male triathlete on endurance performance and cardiovascular and thermoregulatory responses. For this purpose, the subject ingested, in a double-blind random fashion, either a glycerol solution (1.2 g/kg body weight [BW] with 26 mL/kg BW of fluid) or a placebo (26 mL/kg BW of fluid). The subject then performed 2 hr of cycling at 65% VO2max and 25 °C, which was followed by an endurance performance test to exhaustion. During exercise, the subject drank 830 mL of sports drink. Compared to placebo hyperhydration (PH), GH increased total body water (TBW) by 1,033 mL before exercise. After 2 hr of cycling, sweat rate, heart rate and perceived exertion were similar between trials, but GH reduced urine production by 300 mL, prevented hypohydration, and decreased rectal temperature by 0.42 °C. Compared to PH, GH increased endurance performance by 24%, which was associated with a reduced rectal temperature of the order of 0.3 °C. Thus, in this highly trained triathlete, GH better maintained hydration during a 2 hr cycling exercise at 65% VO2max, which reduced core temperature and improved endurance performance. ABSTRACT FROM AUTHOR